The outer membrane proteins based seroprevalence strategy for Brucella ovis natural infection in sheep - Zhang, Tao; Wang, Yu; Li, Yin; Qi, Tingting; Yue, Zhirong; Cao, Lili; Zhou, Bo; Jiao, Huping (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The diagnosis of brucellosis largely relies on tiger red plate agglutination test (RBPT). However, it is difficult to distinguish between natural infection antibody positive and vaccination antibody positive, nevertheless, the identification of specific Brucella species natural infection. Methods Here, we analyzed the structure of main outer membrane proteins (OMPs), OMP25 and OMP31 from Brucella ovis (B. ovis) and Brucella melitensis (B. melitensis), which are the main pathogens of sheep brucellosis, and found the OMP25 and OMP31 could be used as the differential antigens for B. ovis and B. melitensis antibody. Then we expressed the OMP25 from B. ovis (OMP25o) and OMP31 from B. melitensis (OMP31m). Results They have equally efficiency in antibody detection of vaccinated sheep serum, consistent with the RBPT results. However, through epidemiological investigations, we found some RBPT positive samples were negative by the OMP31m based serum antibody detection, but these samples gave positive results by the OMP25o. We verified these OMP31m negative but OMP25o positive samples by B. ovis and B. melitensis specific primers based PCR detection, and all these samples were B. melitensis negative. However, four out of six samples are B. ovis positive. These results showed that we could use the OMP25o and OMP31m to diagnose sheep brucellosis antibody, especially to discriminate the infection of the B. ovis. Discussion Currently, China has not yet approved a vaccine based on B. ovis and B. ovis positive samples should be naturally infected. There should be some implicit transmission of B. ovis in Jilin province. Further epidemiological investigation should be conducted to monitor the B. ovis natural infection.